Do SGLT2 Inhibitors Affect Skeletal Muscle Mass and Strength? A Systematic Review of Body Composition and Functional Outcomes - Turczynowski, Kamil; Turczynowski, Konrad; Lichoń, Jakub; Łyko, Zuzanna; Kuna , Wojciech; Pietrucha , Jakub; Gołdyn , Mateusz; Niski , Jakub; Rutkowska , Anna; Studziński , Dawid (Journal of Education, Health and Sport, 2026)
Background. Sodium–glucose cotransporter-2 inhibitors (SGLT2i) are widely used in the treatment of type 2 diabetes mellitus, chronic kidney disease, and heart failure. Although these agents promote weight loss and improve cardiometabolic outcomes, concerns have emerged regarding potential reductions in skeletal muscle mass and their impact on physical function. Aim. To review current evidence on the effects of SGLT2 inhibitors on skeletal muscle mass, muscle strength, and functional outcomes. Material and methods. A systematic narrative review of English-language studies published between 2020 and 2026 was conducted. Randomized controlled trials, observational studies, and meta-analyses evaluating body composition and functional performance outcomes during SGLT2 inhibitor therapy were included. Results. SGLT2 inhibitors consistently reduced body weight primarily through fat mass loss, while reductions in lean mass were generally small. Skeletal muscle mass and handgrip strength were largely preserved in middle-aged adults, whereas greater variability was observed in older individuals and patients with chronic kidney disease. Evidence suggests that physical activity and adequate nutrition may mitigate potential muscle loss. Conclusions. SGLT2 inhibitors promote favorable body recomposition with predominantly fat mass reduction and minimal effects on muscle function in most patients. Monitoring muscle health and supporting lifestyle interventions may be beneficial in vulnerable populations.